2023
DOI: 10.1002/chem.202301892
|View full text |Cite
|
Sign up to set email alerts
|

A Bifunctional Coordination‐Chain‐Based Hydrogen‐Bonded Framework for Quantitative Enantioselective Sensing

Abstract: Enantioselective sensing is highly crucial and challenging due to the highly similar physical/chemical properties of enantiomers which may have different chemical impact on organism. Luminescent coordination compounds have attracted great attention as sensing materials based on their controllable chemical and electric structures that can be highly matched with the targeted species. To achieve high‐performance enantioselective sensing, the direct synthesis of chiral and luminescent bifunctional coordination com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Recently, the chiral cation L-carnitine was introduced into the pores of NKU-1000 with the second luminescence center of Tb 3 + ion, to generate a bifunctional NKU-1000-CÀ Tb (Figure 5). [38] For electrochemical energy storage application, Li + ions were introduced into the ionic NKU-1000 through guest exchange, to form Li@NKU-1000. [39] Thirdly, the hydrogen-bonded frameworks provide a means to modify the connection modes by inserting metal ions between the building blocks with specific donors to form coordination bonds, resulting in the transformation to coordination compounds.…”
Section: Strategies For Postsynthetic Modified Hydrogen-bonded Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the chiral cation L-carnitine was introduced into the pores of NKU-1000 with the second luminescence center of Tb 3 + ion, to generate a bifunctional NKU-1000-CÀ Tb (Figure 5). [38] For electrochemical energy storage application, Li + ions were introduced into the ionic NKU-1000 through guest exchange, to form Li@NKU-1000. [39] Thirdly, the hydrogen-bonded frameworks provide a means to modify the connection modes by inserting metal ions between the building blocks with specific donors to form coordination bonds, resulting in the transformation to coordination compounds.…”
Section: Strategies For Postsynthetic Modified Hydrogen-bonded Frameworkmentioning
confidence: 99%
“…[39] For the chiral properties, we developed a strategy that introducing chiral cations into an anionic hydrogen-bonded framework through the exchange of the cations inside the pores (Figure 5). [38] The post-synthetically modified NKU-1000-C performs similar Cotton effects with the chiral cation, and can be applied as the enantioselective sensor for small chiral organic molecules, such as potent intermediates for pharmaceuticals and industries, 2-amino-1-propanol and 1,2-propanediol (Figure 11). Detailed sensing mechanism studies revealed that the competitive absorption and Förster resonance energy transfer processes contribute cooperatively to the emission intensity changes, while the post-synthetically modified chiral cations that selectively interact with targeting chiral molecules induces the enantioselective recognition property.…”
Section: Properties Of Postsynthetic Modified Hydrogen-bonded Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…1 HOFs represent a class of crystalline framework structures formed by intermolecular hydrogen bonds between organic or metal-containing molecules, assembled through the synergistic action of other non-covalent interactions such as π–π stacking. 2 Current research efforts focus on these aspects, propelling advancements in various fields including dye adsorption and degradation, 3,4 proton conduction, 5,6 catalysis, 7,8 luminescence phenomena, 9,10 anti-counterfeiting and sensing technologies, 11–16 biological applications, 17–20 gas separation processes, 21,22 enantiomer resolution and separation of aromatic compounds, 23 etc. Since the beginning of the 21st century, MOFs have experienced explosive development, while COFs have recently entered a stage of rapid growth.…”
Section: Introductionmentioning
confidence: 99%
“…9 Despite the large potential for the development of MOFs as fluorescent chiral sensors, only a handful of studies have been reported. 5,9–18 A challenge facing MOF-based fluorescent chiral sensors is engendering a high degree of enantioselectivity in interactions with enantiomeric pairs.…”
Section: Introductionmentioning
confidence: 99%